DISCURSIVE STRATEGIES IN HACKTIVISM DISCOURSE: REVEALING IDEOLOGY IN AL-HAKIRZ AL-MUSLIMUN’S HACKING THREAT - Reflinaldi, Reflinaldi; Ilyas, Erizal; Rahmi, Awliya; Rezi, Melisa; Syahidin, Amal; Aini, Resty Syahrotul (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2024)
This study explores the underlying ideology in the hacktivism discourse of al-hākirz al-muslimūn (MH), a group of Muslim hackers. The objective was to uncover the discursive strategies used by MH in its cyber threats, focusing on how they construct their identity and position themselves in opposition to perceived threats. A critical qualitative design was employed to analyze three videos from the Hacker News YouTube channel, using the ideological square framework as the theoretical lens for data analysis. The results of macroanalysis show that MH used the basic strategy of emphasizing positive 'us' on 11 data (14.67%), emphasizing negative 'them' on 31 data (41.33%), and de-emphasizing positive 'them' on 33 data (44.00%). In the microanalysis dimension, the rhetorical discursive strategies found include actor description amounting to 23 data (31.08%), consensus with a total of 2 data (2.70%), evidentiality reaching 5 data (5.41%), example/illustration with a total of 7 data (9.46%), values expression reaching 14 data (18.92%), number game with a total of 4 data (5.41%), and victimization-criminalization amounting to 20 data (27.03%). The ideological analysis indicated that MH’s discourse is characterized by anti-imperialism, reflecting their defense of oppressed populations and the use of hacking as a form of retribution. Additionally, anti-extremism was evident in the group’s critique of actions perceived as insults to Islam, often tied to extremist ideologies. This study contributes to the understanding of hacktivism as a form of digital activism, emphasizing its role in shaping political discourse and public opinion through cyber threats. It provides insights into the ideological motivations behind hacktivism, showing how groups like MH use digital platforms to challenge global political structures. The implications of this study are significant for future research into hacktivism, particularly in exploring the broader impact of such discourse on global politics, the ethical dimensions of cyber activism, and the potential of multimodal discourse analysis to examine the interplay of textual, visual, and audiovisual elements in discourse interpretation. By applying multimodal discourse analysis, future researchers could explore how audio, visual, and color codes contribute to shaping meaning in hacktivist narratives. This study highlights the complexity of hacktivism and its potential to reshape political narratives and activism in the modern world.